Renal Urotensin II System Plays Roles in the Regulation of Blood Pressure in Dahl Salt-Resistant Rat - Fei Wu; Guanjong Chen; Aihua Zhang; Yang Yu; Minhua Fan; Chaoshu Tang (International Journal of Hypertension)
Introduction. Dahl salt-resistant (SR) animal models are similar to peritoneal dialysis patients with fluid volumes overload with normal blood pressure in hemodynamic profiles. We will verify the roles of UII in the regulation of blood pressure in these animal models. Methodology. The Dahl salt-sensitive (SS) and SR rats and UII receptor gene knocked out (KO) mice were placed on a high-salt diet. Renal tissues were performed for the expression of UII in Dahl groups. Results. After high-salt diet for 6 weeks, the systolic blood pressure (SBP) in SR group was significantly lower, accompanied with higher urinary UII levels, higher 24-hour urinary sodium excretion, and higher urinary creatinine clearance in the SR rats in comparison to SS group. The expressions of UII and UT were both upregulated in the kidney tissues of SR group in comparison to SS group (P<0.05). After high-salt diet for 8 weeks, the SBP of the KO group is significantly higher than that of the wild type group. Conclusion. We first demonstrate that renal UII system can play important roles in the regulation of blood pressure in Dahl SR rats which can be highly correlated to its effect on renal tubular sodium absorption.